Another reading. A contribution to the reading pro-blem in library science - ALFARO LÓPEZ, HÉCTOR GUILLERMO (Investigación Bibliotecológica. Archivonomía, bibliotecología e información, 2007)
THIS FOCUS ON THE READING PROBLEM INTENDS TO SHOW LIBRARY SCIENCE AS A DISCIPLINE WHERE OTHER DISCIPLINES WHOSE PERSPECTIVES HAVE ALSO HANDLED THE LECTURE SUBJECT CONVERGE, LIKE PSYCHOLOGY. THIS INSTANCE EXPLAINS WHY THE BASIC CONTEMPORARY LIBRARY SCIENCE'S CONCEPTION OF READER AND READING NEEDS TO BE WIDENED AND COMPLETED WITH THE CONTRIBUTIONS OF OTHER DISCIPLINES IN ORDER TO REGAIN ITS HUMANISTIC FOUNDATION. IT ALL FINALLY DERIVES FROM A COMPREHENSION OF THE LUDIC DIMENSION INVOLVED IN READING.